KONTRIBUSI DAYA LEDAK OTOT LENGAN, KELENTUKAN DAN KOORDINASI MATA-TANGAN TERHADAP KETEPATAN SMASH ATLET BULUTANGKIS PB. BINTAMA KERINCI - Roki Putra (Ensiklopedia of Journal, 2019)
Based on writer observations in field showed the smash ability possessed by the athletes of PB. BINTAMA Kerinci are still low. The porpuse of this research is to see the explosive power contribution of arm muscle, flexibility and coordination of hand-eye to smash accuracy of badminton athlete.. This research method is a quantitative method using correlational research design. The population in this study amounted to 34 people. The sampling technique is done by proportional random sampling with a number of sample which is used by 30 people. The data collected by using ball medicine instrumen contribution of arm muscle, flexiometer to measure flexibility, ball Werfen und fangen for measuring coordination eye-hand, and jump smash test to smash accuracy. The data analysis use simple correlation analysis technigue, multiple regression, and partial test. The result showed that: (1) the explosive power of arm muscles have a positive relationship to smash accuracy with taritmatic = 5,624 > ttable = 2,048 and contributed 40,28% to the smash accuracy. (2) flexibility has a positive relationship to smash accuracy with taritmatic = 3,151 > t table = 2,048 and contributed 26,17% to smash accuracy. (3) eye-hand coordination has a positive relationship to smash accuracy with taritmatic = 3,022 > t table = 2,048 and contributed 24,60% to smash accuracy. (4) The arm muscle explosive power, flexibility, and eye-hand coordination has a positive relationship to smash accuracy with Faritmatic (26,04)> F table (2,89) and contributed jointly by 75% to smash accuracy.